Deubiquitination of EGFR by Cezanne-1 contributes to cancer progression - Pareja, Fresia; Aulmann, Sebastian; Sinn, Peter (Oncogene, 2012)
Once stimulated, the epidermal growth factor receptor (EGFR) undergoes self-phosphorylation, which, on the one hand, instigates signaling cascades, and on the other hand, recruits CBL ubiquitin ligases, which mark EGFRs for degradation. Using RNA interference screens, we identified a deubiquitinating enzyme, Cezanne-1, that opposes receptor degradation and enhances EGFR signaling. These functions require the catalytic- and ubiquitin-binding domains of Cezanne-1, and they involve physical interactions and transphosphorylation of Cezanne-1 by EGFR. In line with the ability of Cezanne-1 to augment EGF-induced growth and migration signals, the enzyme is overexpressed in breast cancer. Congruently, the corresponding gene is amplified in approximately one third of mammary tumors, and high transcript levels predict an aggressive disease course. In conclusion, deubiquitination by Cezanne-1 curtails degradation of growth factor receptors, thereby promotes oncogenic growth signals.